Stakeholder Theory for Sustainable Cities and Society: A Humanist and Environmental approach for integrating People, Institutions, and Environmental Ecosystems - Donizete Beck (Studia Ecologiae et Bioethicae)
It needs to be clarified in the literature as to how humanism could embrace environmental ecosystems in cities and society. Some scholars argue that Stakeholder Theory could help bridge the environmental ecosystems under a humanist approach. For this reason, this study aims to fill this gap by exploring how Stakeholder Theory and Humanism can be connected to the fostering of sustainable development in cities and society. The main findings highlighted in the urban and societal contexts the role of stakeholder and humanist responsibility, the role of stakeholder consensus about humanist themes and environmental issues, and last but not least important, the need to consider the environment as a non-human stakeholder in social and urban governance. These directions should also be further detailed and explored in the multi/interdisciplinary fields of Sociology, Philosophy, Social Sciences, Humanities, Political Science, and Urban Studies. Therefore, this study provided a conceptual framework of three propositions which revealed that a stakeholder-oriented and humanism-oriented governance can embrace environmental concerns in cities and societies. In this way, consensus, responsibility, and considering the environment as a non-human stakeholder are critical elements in urban and social governance.